1989
DOI: 10.1080/0885625890040201
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and adjustment problems of young developmentally delayed children

Abstract: As part of an ongoing longitudinal study of developmental delay (DD), 35 six-yearold children with delays of unknown aetiology were assessed with measures of cognitive, language and educational competence. Their parents provided detailed information about their self-help and personal-social competencies, behaviour problems and temperament. As a group, the DD children evidenced high rates of behaviour problems, but there was considerable within-group variability in intensity and pattern of problems. Low relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In general, parents tend to rate their children higher in developmental status than do professionals (Sexton, Thompson, Perez, & Rheams, 1990;Sheehan, 1988). There is, however, relatively little evidence testing parentteacher concordance about behavior problems, despite the findings that as a group, children with developmental disabilities evidence more behavior problems than do nonreferred peers (Keogh, Bernheimer, Haney, & Daley, 1989;Thompson, 1986). Cuskelly and Dadds (1992) investigated mothers', fathers', and teachers' ratings of children with Down syndrome and their siblings, using the Revised Behavior Problem Checklist (Quay & Peterson, 1983); all three rater sources found that children with Down syndrome had higher problem scores than their siblings without Down syndrome.…”
Section: Studies Of Children With Cognitive Delaysmentioning
confidence: 94%
“…In general, parents tend to rate their children higher in developmental status than do professionals (Sexton, Thompson, Perez, & Rheams, 1990;Sheehan, 1988). There is, however, relatively little evidence testing parentteacher concordance about behavior problems, despite the findings that as a group, children with developmental disabilities evidence more behavior problems than do nonreferred peers (Keogh, Bernheimer, Haney, & Daley, 1989;Thompson, 1986). Cuskelly and Dadds (1992) investigated mothers', fathers', and teachers' ratings of children with Down syndrome and their siblings, using the Revised Behavior Problem Checklist (Quay & Peterson, 1983); all three rater sources found that children with Down syndrome had higher problem scores than their siblings without Down syndrome.…”
Section: Studies Of Children With Cognitive Delaysmentioning
confidence: 94%
“…These SIP deficits could explain social difficulties (van Nieuwenhuijzen et al, 2009;van Nieuwenhuijzen & Vriens, 2012) and affect emotion regulation, social maladjustment or the risk of behavioral problems (Baurain & Nader-Grosbois, 2013;Leffert & Siperstein, 1996;van Nieuwenhuijzen et al, 2004). Such maladaptive behaviors in turn affect social competences and autonomy (Crnic, Hoffman, Gaze, & Edelbrock, 2004;Keogh, Bernheimer, Daley, & Haney, 1989;Merrell & Holland, 1997;Zion & Jenvey, 2006). Concretely, by being resistant to others, children with IDs experience less cooperative or prosocial behaviors during social interaction (Kasari & Bauminger, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Behavior problems remained relatively stable over time, although as noted by Keogh, Ratekin, and Bernheimer (in review) the expression of problems changed as the children grew older, moving from immaturity to problems associated with behavioral disturbance. Details of child findings may be found in reports by Bernheimer and Keogh (1986), Bernheimer, Gallimore, & Kaufman (in press), and Keogh et al (1989).…”
Section: Eligibility For Services Upon Entry Into Elementary School: mentioning
confidence: 98%